Pengaruh Gamifikasi, Promosi dan Kemudahan Penggunaan terhadap Loyalitas Konsumen di Aplikasi Shopee : Survei pada Komunitas Shopee Games Indonesia - Rika Pramesti; Mutya Paramita Pratita (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of gamification, promotion, and ease of use on consumer loyalty in the Shopee application, focusing on members of the Shopee Games Indonesia Community. The background of this research lies in the increasingly intense competition in the e-commerce industry, which requires companies to develop innovative strategies to retain customers. One of the strategies implemented by Shopee is gamification through interactive game features, diverse promotional activities, and a simple, user-friendly application interface. This research employed a quantitative approach, with primary data collected through questionnaires distributed to 97 respondents who actively used Shopee Games features. The data were analyzed using multiple linear regression to test the proposed hypotheses. The results indicate that gamification, promotion, and ease of use significantly affect consumer loyalty. These findings highlight that the success of e-commerce applications in retaining customers does not only rely on product quality, but also on creating enjoyable user experiences, relevant promotional strategies, and innovative features that can enhance user engagement. Therefore, the implementation of gamification and promotion strategies supported by ease of use can serve as key factors in improving customer loyalty toward Shopee.